2023
DOI: 10.1038/s41586-023-05874-3
|View full text |Cite
|
Sign up to set email alerts
|

Lung adenocarcinoma promotion by air pollutants

Abstract: Environmental carcinogenic exposures are major contributors to global disease burden yet how they promote cancer is unclear. Over 70 years ago, the concept of tumour promoting agents driving latent clones to expand was rst proposed. In support of this model, recent evidence suggests that human tissue contains a patchwork of mutant clones, some of which harbour oncogenic mutations, and many environmental carcinogens lack a clear mutational signature. We hypothesised that the environmental carcinogen, <2.5μm par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(98 citation statements)
references
References 74 publications
2
69
0
Order By: Relevance
“…Multiple studies demonstrated that neighborhoods with high concentrations of African American or Hispanic patients have higher exposures to environmental carcinogens, including particulate matter less than 2.5 μg (PM 2.5 ), nitrogen oxide, benzenes, and carbon monoxide . The association of PM 2.5 , nitrogen oxide, and other pollutants with lung cancer risk is well established . Although we did not find a specific article that evaluated the direct link between the increased risk of environmental carcinogens that African American and Hispanic/Latino individuals experience with lung cancer risk, a secondary analysis of patients with lung cancer in a single center in California found an association between neighborhood PM 2.5 and an aggressive non–small cell lung cancer somatic ( TP53 ) mutation.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Multiple studies demonstrated that neighborhoods with high concentrations of African American or Hispanic patients have higher exposures to environmental carcinogens, including particulate matter less than 2.5 μg (PM 2.5 ), nitrogen oxide, benzenes, and carbon monoxide . The association of PM 2.5 , nitrogen oxide, and other pollutants with lung cancer risk is well established . Although we did not find a specific article that evaluated the direct link between the increased risk of environmental carcinogens that African American and Hispanic/Latino individuals experience with lung cancer risk, a secondary analysis of patients with lung cancer in a single center in California found an association between neighborhood PM 2.5 and an aggressive non–small cell lung cancer somatic ( TP53 ) mutation.…”
Section: Resultsmentioning
confidence: 73%
“…22,23,29,39,40 The association of PM 2.5 , nitrogen oxide, and other pollutants with lung cancer risk is well established. 44,45 Although we did not find a specific article that evaluated the direct link between the increased risk of environmental carcinogens that African American and Hispanic/Latino individuals experience with lung cancer risk, a secondary analysis of patients with lung cancer in a single center in California found an association between neighborhood PM 2.5 and an aggressive non-small cell lung cancer somatic (TP53) mutation. In this cohort, census block groups with higher minority populations had statistically higher PM 2.5 exposure levels.…”
Section: Housing and Built Environmentmentioning
confidence: 94%
“…Single-cell-type exposomics offers several applications with the potential to drive significant discoveries. For instance, one could conduct single-cell exposome analysis on different lung cell types to scrutinize their differential responses to particulate matter exposures . The expected findings could demonstrate that distinct cell types exhibit varying adaptive metabolic responses, underlining the importance of cell-specific analyses in deciphering complex pathophysiological processes.…”
Section: Single-cell-type Exposomicsmentioning
confidence: 99%
“…Atmospheric aerosols possess complex compositions of organic and inorganic components that dictate their phase and mixing states. With variations of the ambient relative humidity (RH), changes in aerosol water content led to phase transitions such as effloresce, deliquescence, and liquid–liquid phase separation. Effloresced particles, formed via crystallization of dissolved salts upon water evaporation, can directly or indirectly affect the radiative forcing, cloud formation, and atmospheric chemistry due to the changes in physicochemical properties (e.g., morphology, size, refractive index). Therefore, aerosol efflorescence plays a crucial role in atmospheric processes and has profound impact on climate, air quality, , and human health. …”
Section: Introductionmentioning
confidence: 99%